2019
DOI: 10.1016/j.heliyon.2019.e01598
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tris(2-carboxyethyl) phosphine reduction conditions for fast analysis of total biothiols in mouse serum samples

Abstract: In this study, we investigated suitable conditions for the reduction of disulfides in mouse serum samples by tris(2-carboxyethyl) phosphine (TCEP) for fast analysis of total biothiols. Disulfides were reduced with TCEP, and then, thiols were derivatized with the fluorogenic reagent, ammonium 7-fluoro-2,1,3-benzoxadiazole-4-sulfonate (SBD-F). Interference peaks on chromatograms of mouse serum samples disappeared when the TCEP reaction was conducted on ice instead of at room temperature, which is used classicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Pretreatment of mouse urine samples and standard solutions was based on methodology from a previous report [18]. In brief, the samples were incubated with tris(2-carboxyethyl)phosphine (TCEP) to reduce disulfide bonds into thiols.…”
Section: Sample Pretreatmentmentioning
confidence: 99%
“…Pretreatment of mouse urine samples and standard solutions was based on methodology from a previous report [18]. In brief, the samples were incubated with tris(2-carboxyethyl)phosphine (TCEP) to reduce disulfide bonds into thiols.…”
Section: Sample Pretreatmentmentioning
confidence: 99%
“…The determination of free cysteamine in plasma requires reducing disulfides prior to the analysis. Several reducing agents have been proposed, including dithiothreitol (DTT) and Tris(2-carboxyethyl) phosphine (TCEP) [14,30,31]. In the present study, in order to selectively and quantitatively reduce disulfide bonds, we used TCEP as previously described in [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in order to selectively and quantitatively reduce disulfide bonds, we used TCEP as previously described in [31]. Optimal TCEP-reducing conditions for measuring total biothiols in mouse serum samples have been previously described in [30,32,33]. These studies showed that TCEP reduces disulfide bonds as effectively as dithiothreitol (DTT) but offers addi-tional advantages because it is non-volatile, odorless, and, unlike most other reducing agents, resistant to air oxidation.…”
Section: Discussionmentioning
confidence: 99%